Genomic characterization of multidrug-resistant clinical Acinetobacter baumannii isolates from a hospital in Paraguay - Sánchez-Urtaza, Sandra; Alfonso-Alarcón, Laura; Arazo del Pino, Rocío; Burgwinkel, Tessa; Ocampo-Sosa, Alain; Gonzalez, Ruth; Xanthopoulou, Kyriaki; Higgins, Paul G.; Alkorta, Itziar; Gallego, Lucia (Frontiers in Cellular and Infection Microbiology, 2025)
Acinetobacter baumannii is a clinically important pathogen capable of causing serious nosocomial infections and acquiring resistance to antimicrobials, particularly carbapenems, making treatment difficult and prolonging hospital stays. In Latin America, high carbapenem-resistance rates have been described among A. baumannii isolates, however, Paraguay is one of the countries with limited data in this regard. Therefore, we aimed to investigate resistance rates of A. baumannii isolates from the National Hospital of Itaugua (NHI), Paraguay, from their database of 2022, and from December 2023 to February 2024, and to study in detail a representative group of multidrug-resistant clinical isolates. For this purpose, data were analyzed considering diagnostic, sample type and antimicrobial susceptibility. Eight A. baumannii isolates recovered from patients in six separate ICUs in 2024 were then selected and subjected to susceptibility testing using VITEK® and to short- and long-read sequencing, and clonality, resistome, virulome and plasmidome of the isolates were investigated. IC2 (ST2 Pasteur, ST1816/195 Oxford and ST872 Oxford) was the predominant clone among the Paraguayan isolates, and a single isolate belonging to clone IC5 (ST79 Pasteur and ST1283 Oxford) was also identified. The carbapenemase gene blaOXA-23 was located in transposons Tn2006 and Tn2008. Additionally, other antibiotic resistance genes conferring resistance to aminoglycosides, macrolides, sulfonamides, chloramphenicol, tetracyclines and trimethoprim were identified, and were found embedded in genetic environments containing mobile genetic elements. Multiple virulence genes were also detected, mainly promoting biofilm formation and immune system modulation. Plasmid analysis showed the presence of plasmids ranging in size from 2.27 to 10.74 Kb. This work describes the dissemination of the emerging clone IC2 in Paraguay and offers a detailed analysis of the resistome, virulome and plasmidome of carbapenem-resistant A. baumannii strains. The results obtained highlight the importance of correctly characterizing these multidrug-resistant pathogens to develop infection prevention and control strategies at hospital level.